Performance Analysis of 5G Waveform – Bi-Orthogonal Frequency Division Multiplexing under Real Fading Condition Simulations - Sekhar Yarrabothu, Ravi; Satrasupali, Sivaji; Gutha, Lakshmi (International Journal of Engineering and Technology, 2018)
4G LTE communication system uses OFDM and for resource allocation control channels like PRACH is used. Around 6% bandwidth is getting used for this PRACH procedure and due to OFDM requirement of strict synchronization, short messaging become tedious and cause power wastage due to the control traffic for every message. The main challenge for 5G communications is to handle the transmission of extremely asynchronous data and control traffic in one go. Existing OFDM based systems have the drawback of very sensitive to the time and frequency offsets and in turn results in synchronization errors. To overcome this challenge, it has been adopted a new waveform based on Bi-orthogonal Frequency Division multiplexing (BFDM) which supports the Internet of Things (IoT) sporadic traffic. In this paper, BFDM principles, behaviour of BFDM under various channel conditions, Matlab simulation results pertaining to the performance of BFDM against the existing OFDM are discussed. The simulation results shows that the Symbol Error Rate of the BFDM system is less than the OFDM under time varying fading conditions such as Extended Pedestrian A (EPA), Extended Vehicular A (EVA), Extended Typical Urban(ETU) models.